Being Human During COVID-19 (Bristol University Press, 2022)
Cutting across disciplines from science and technology studies to the arts and humanities, this thought-provoking collection engages with key issues of social exclusion, inequality, power and knowledge in the context of COVID-19. The authors use the crisis as a lens to explore the contours of contemporary societies and lay bare the ways in which orthodox conceptions of the human condition can benefit a privileged few. Highlighting the lived experiences of marginalized groups from around the world, this is a boundary-spanning critical intervention to ongoing debates about the pandemic. It presents new ways of thinking in public policy, culture and the economy, and points the way forward to a more equitable and inclusive human future. Chapter 12 is available Open Access via OAPEN under CC-BY-NC-ND licence.